Bittere Kirschen - Danquart, Didi; Weiland, Stephan; Kuckart, Judith, 1959-; Stieblich, Anna; noirfilm Filmproduktion; Eastwest Film Distribution GwBH ([Karlsruhe, Germany] : noirfilm Filmproduktion, 2011)
After her mother's death, Lena decides to quit her acting career and returns to her small hometown in Germany. There, she is reunited with her boyfriend who wants to marry her. But she's afraid of the commitment. She also meets Julius, her mother's childhood friend who starts telling her about Auschwitz in 1944, "where it all began", as her mother used to say. Willing to find answers to the questions she was never able to ask her mother, Lena decides to go to Poland. Joined by Julius and Father Richard Franzen, a priest who falls in love with her, Lena's trip through unknown Polish landscapes becomes a journey into the past. --
Originally released as a motion picture in 2011.
Based on: Lenas Liebe / Judith Kuckart.
Anna Stieblich, Martin Lüttge, Wolfram Koch, Roland Kukulis
Cinematographer, Johann Feindt; editor, Silke Botsch; music, Cornelius Schwehr.
In German with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 12, 2015).
Keywords: Auschwitz (Concentration camp) -- Drama; Actresses -- Germany -- Drama; Automobile travel -- Drama; Memory -- Drama; Man-woman relationships -- Drama; Road films; Film adaptations; Feature films; Internet videos; Streaming video